Faktor Yang Mempengaruhi Ketidakpatuhan Minum Obat Antihipertensi di Wilayah Kerja Puskesmas Nguter Kabupaten Sukoharjo - Sirait, Chronika Kesya; Adi, Mateus Sakundarno; Suhartono, Suhartono; Muh, Fauzi; Hudayani, Rina (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Adherence to treatment is crucial for those with hypertension, particularly in order to avoid consequences. Although there is no treatment for hypertension, it must always be managed to prevent it from becoming worse and becoming a condition that can lead to death and disability.Methods: Studi case-control was used in this research. Patients with hypertension who had been diagnosed by a doctor in Nguter Sub-district constituted the study population. The total sample was 220 with a ratio 1:1. Accidental sampling was used in the sampling procedure according to the predetermined inclusion and exclusion criteria. Questionnaires were used to collect data. The chi square test was used for bivariat, and logistic regression for multivariate analysis.Result: Based on the results of the analysis, it was found that there were three factors that had a significant impact on the level of non-adherence of hypertension patients in taking medication in the Nguter District area: a low motivation to seek treatment (p=0,000), a lack of support from family (p=0,009), and a lack of active role of health workers (p=0,042).Conclusion: Treatment motivation is the most influential factor on non-adherence to taking antihypertensive medication (p= 0,000; OR= 3,49; 95% CI= 1,81–6,73).